The polluted atmospheres of cool white dwarfs and the magnetic field connection - Kawka, Adéla; Vennes, S. (Wiley-Blackwell Publishing Ltd., 2014)
We present an analysis of X-Shooter spectra of the polluted hydrogen-rich white dwarfs (DAZ) NLTT 888 and NLTT 53908. The spectra of NLTT 53908 show strong, Zeeman-split calcium lines (Ca II H&K and Ca I?4226) and the star appears to be a close relative of the polluted magnetic white dwarf (DAZH) NLTT 10480, while the spectra of NLTT 888 show narrow lines of calcium and iron. A comparison of the DAZ NLTT 888 and the DAZH NLTT 53908 with other class members illustrates the diversity of environment and formation circumstances surrounding these objects. In particular, we find that the incidence of magnetism in old, polluted white dwarfs significantly exceeds that found in the general white dwarf population which suggests a hypothetical link between a crowded planetary system and magnetic field generation. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.